2008
DOI: 10.4049/jimmunol.180.9.6064
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Normal and Malignant Kit Signaling by a Bispecific Antibody Linking Kit with CD300a

Abstract: Through its receptor Kit (CD117), stem cell factor (SCF) critically regulates human mast cell (MC) differentiation, survival, priming, and activation. The dominance of SCF in setting these parameters compels stringent contra-regulation to maintain a balanced MC phenotype. We have synthesized a library of bispecific Ab fragments to examine the effect of linking Kit with CD300a. In this study, we report that CD300a exerts a strong inhibitory effect on Kit-mediated SCF-induced signaling, consequently impairing MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…Intriguingly, upon cross-linking of the receptor with mAbs, only SHIP-1 associated with CD300a in the same cell type (19). Furthermore, immunoprecipitation of CD300a from human mast cells that were treated with Kit-CD300a, a bispecific Ab fragment linking Kit with CD300a, induced its tyrosine phosphorylation and the recruitment of SHIP but not SHP-1 (53). Triggering of CD300a with mAbs induced weak phosphorylation of SHIP-1 on human basophils, but the phosphorylation status of SHP-1 and SHP-2 was not tested (21).…”
Section: Mechanisms Of Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…Intriguingly, upon cross-linking of the receptor with mAbs, only SHIP-1 associated with CD300a in the same cell type (19). Furthermore, immunoprecipitation of CD300a from human mast cells that were treated with Kit-CD300a, a bispecific Ab fragment linking Kit with CD300a, induced its tyrosine phosphorylation and the recruitment of SHIP but not SHP-1 (53). Triggering of CD300a with mAbs induced weak phosphorylation of SHIP-1 on human basophils, but the phosphorylation status of SHP-1 and SHP-2 was not tested (21).…”
Section: Mechanisms Of Signalingmentioning
confidence: 99%
“…Some investigators demonstrated that coligation of CD300a with FceRI is essential for the CD300a-mediated inhibitory signal (52). Instead, others showed that there is no requirement for the coligation of CD300a with the activating receptor for CD300a to inhibit the FceRI-mediated activation signal, despite the fact that coligation increased the inhibitory effect (19,53). Interestingly, the effect on mast cell survival did not change significantly when CD300a was coligated with Kit (19).…”
Section: Mechanisms Of Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to mast cells, it has been shown that cross-linking of CD300a with the high affinity receptor for IgE (FceRI) down-regulates IgE-mediated mast cell degranulation and cytokine production (17,18), whereas linking to c-Kit abrogates c-Kit-mediated cell differentiation, survival, and activation (19). Furthermore, CD300a shares 80% structural homology with CD300c (8,9), whose function remains to be elucidated.…”
mentioning
confidence: 99%